Assessment of the Environmental Impact of a Car Tire throughout Its Lifecycle Using the LCA Method - Piotrowska, Katarzyna (Materials (Basel), 2019)
There are numerous threats to the natural environment that pose a significant risk both to the environment and to human health, including car tires. Thus, there is a need to determine the impact of the life cycle of car tires on the environment, starting with the processes of raw materials acquisition, production, and ending with end-of-life management. Therefore, the authors of this study chose to do research on passenger car tires (size: P205/55/R16). As part of the research, the life cycle assessment (LCA) of traditional car tires was performed with the use of the Eco-indicator 99, cumulative energy demand (CED), and Intergovernmental Panel on Climate Change (IPCC) methods. The level of negative effects was determined for the life cycle of a tire and its particular stages: Production, use, and end of life. The negative impact on the atmosphere, soil, and water, as well as on human health, the environment, and natural resources was also investigated. The results show that the most energy-absorbing stage of a car tire life cycle is the use stage. It was found that the most harmful impact involves the depletion of natural resources and emissions into the atmosphere. Recycling car tires reduces their negative environmental impact during all their life cycle stages.